Marine Jellyfish Collagen and Other Bioactive Natural Compounds from the Sea, with Significant Potential for Wound Healing and Repair Materials - Ana-Maria Pesterau; Antoanela Popescu; Rodica Sirbu; Emin Cadar; Florica Busuricu; Ana-Maria Laura Dragan; Carolina Pascale; Ana-Maria Ionescu; Claudia Florina Bogdan-Andreescu; Marius-Daniel Radu; Cezar Laurentiu Tomescu (Marine Drugs)
Skin health must be ensured at all times in the case of wounds when the skin is subjected to traumatic actions that require multiple wound-healing measures. Wound healing is a complex, multi-phase biological process critical for restoring skin integrity after trauma. This study investigates the development and evaluation of a novel composite hydrogel formulated from collagen peptides extracted from the jellyfish Rhizostoma pulmo and hydroethanolic extracts from the brown alga Cystoseira barbata, both sourced from the Romanian Black Sea coast. Throughout the work, the characteristics due to the biochemical compositions of the extracts from the brown alga C. barbata and from the jellyfish R. pulmo are highlighted as important, emphasizing the content of polysaccharides, proteins, and lipids. Total phenol content was analyzed for three extracts from natural products. The biochemical composition, antioxidant, antimicrobial, and in vitro wound-healing properties of the components and their composite (JPC-ALG) were assessed. The rheological behavior and optical microscopy studies of collagen hydrogels were prepared. The general mechanisms of wound healing with the involvement of polysaccharides and collagen peptides existing in all categories of extracts were highlighted. The study of the effects of JPC-ALG composites and individual extracts on fibroblast and keratocyte cell lines is also presented. Results demonstrated that the composite exhibited synergistic effects, enhancing fibroblast and keratinocyte migration and proliferation, key factors in wound closure. The findings support the potential application of this marine-derived bioactive composite as a promising biomaterial for wound-healing therapies.